Interpreting in Early Modern Diplomacy: Occasional Mobility and the Liminal Spaces of Trust - Rizzi, Andrea (Renaissance and Reformation / Renaissance et Réforme, 2021)
In this article, I examine the relationship between mobility and trust in the work and life of a wide range of early modern diplomatic interpreters. I address this relationship by bringing together archival material unearthed by literary scholars and social historians: specifically, historians of diplomacy, translation, and interpreting. I seek to address these documents from the perspective of occasional dragomans who found themselves performing the often-dangerous role of intercultural mediation in exchange for money, an improved social status, or freedom.